Traumatic Optic Neuropathy: Our Experience with Combined Therapy - Kumar, Sudesh; Joshi, Amit; Tuli, Rajeev; Chauhan, Narvir (Indian Journal of Neurotrauma, 2021)
Objective Traumatic optic neuropathy (TON) is an important cause of severe vision impairment after sustaining a closed head injury. This study describes the safety and efficacy of combined therapy in the management of TON.Methods A retrospective analysis of 23 consecutive cases of unilateral TON managed with combined therapy (steroid and surgery) were performed. Statistical analysis of patient characteristic, timing of vision loss, radiological and intraoperative findings, and pre- and post-treatment vision were compared to assess the prognostic factors.Results Seventeen patients (85%) had vision improvement with combined therapy. Three patients (15%), who recorded no improvement, initially presented with no perception of light, and loss was sudden and immediate. With steroids, 9 patients improved, all of them presented with perception of light (PL) or better and vision improved to (6/6 in five, 6/9 in one, 6/18 in 3). Eleven patients (6 PL–ve and 5 PL + ve after failed steroid therapy) underwent endoscopic optic nerve decompression and eight had improvement in vision. The status of vision at presentation was only statically significant prognostic factor (p < 0.02). Others prognostic factors, for example, time of starting treatment, surgery, and presence of fracture in optic canal, were not found statistically significant (p > 0.05). There were no significant intra- and postoperative complications.Conclusion Combined therapy is safe and effective in management of TON. Mild form injury with some preserved vision at presentation respond well to steroids, while endoscopic nerve decompression should be reserved in cases with failed steroid therapy.
Keywords: combined therapy; endoscopic decompression; steroid; traumatic optic neuropathy; visual outcome